Return-to-work after vocational rehabilitation: challenges and perspectives (Research, Society and Development, 2022)
Objective: This study aimed to understand the process of return-to-work of workers cared by the Vocational Rehabilitation Program in a countryside city in the state of São Paulo. Methodology: It is a qualitative, descriptive and exploratory study, carried out in two phases with workers discharged between 2009 and 2020: documental analysis to identify workers’ profiles and main causes of sick leave; and individual interviews by telefone, guided by a script of previously structured questions. Profiles and leaving causes were analyzed through descriptive analysis, and the interviews through thematic content analysis. Results: From 2009 to 2020, 263 workers returned to work: 84 women and 179 men. Most of them suffered of musculoskeletal disorders and injuries related to work accidents. Among these, 192 workers returned to work in different position and 71 to the same one, but in different activities. Eleven workers were interviewed, which resulted in three categories of analysis: challenging and poorly articulated return-to-work process; strengths and weakness of the Vocational Rehabilitation Program; strengthening the Vocational Rehabilitation Program can transform the return-to-work process. Conclusion: The abovementioned study emphasized the Program limitations and redesign necessity, besides the implantation of dialogue with employers, especially because of early discharge and lack of return-to-work surveillance.